ANALYSIS OF DEIXIS IN STEPHEN COLBERT’S COMMENCEMENT SPEECH - Astika Wisnu Wardani; Siska Rizkiani (IKIP Siliwangi, 2021)
The aims of this study is to determine the five types of deixis used by Stephen Colbert in his speech at the Wake Forest Graduating Class of 2015. In this study, qualitative descriptive methods was applied and video was choosen as the instrument of data collection. This data were analyzed based on deixis types suggested by Levinson (1983) and Yule (1996).The type of deixis most frequently used by Stephen Colbert in his speech was a person deixis totaling 232 words dominated by the word ‘I am’. Time deixis 26 words, place deixis nine words, discourse deixis 48 words, and social deixis 34 words. With a total of 349 frequencies found in all five types of deixis in Stephen Colbert's commencement speech.Keywords: Pragmatic, deixis, speech.